Learning to Recognize and Understand AT-TIIN Chapter Through Cooperative Learning Model in Elementary School - Nuraini Nuraini; Tri Kasih (Universitas Tanjungpura, 2022)
This study aims to increase students' knowledge and understanding of the At-Tiin chapter. The research approach was Classroom Action Research (CAR). CAR is a way of determining how to do it with cycles. Data collection with CAR, especially sixth grade, which amounted to 26 students in elementary school. After administering cycle I, 13 students passed with a percentage of 50%. Those who have not passed amounted to 13 students with a percentage of 50%. Then we continued to cycle II with better planning and implementation using the cooperative learning model. There were 24 students passed with a percentage of 92%. Those who have not passed amounted to 4 students with a percentage of 8%.